2011
DOI: 10.1007/s10637-011-9654-0
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation taxanes effectively suppress subcutaneous rat lymphoma: role of disposition, transport, metabolism, in vitro potency and expression of angiogenesis genes

Abstract: The study investigated possible mechanisms by which second-generation taxanes, established as significantly more effective than paclitaxel in vitro, suppress a rat lymphoma model in vivo. The studied mechanisms included taxane pharmacokinetics, expression of genes dominating their metabolism (Cyp3a1/2) and transport (Abcb1) and genes controlling tumour angiogenesis (growth factors and receptors). SB-T-1214, SB-T-12854 and IDN5109 suppressed rat lymphoma more effectively than paclitaxel, SB-T-12851, SB-T-12852,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…SB-T-12854 induced cells death in breast cancer cell lines examined (Figure 2). The taxane has also been shown to be effective in cell death induction in other cancer cell lines (7,42). The effect of SB-T-12854 on the growth and survival of breast cancer cells was similar to the effect of previously studied novel non-fluorinated taxane SB-T-1216 (31,32).…”
Section: Figure 4 Effect Of Sb-t-12854 On the Level Of Proteins Of The Bcl-2 Family In Sk-br-3 Mcf-7 And T47d Cells Ie (A) Proapoptotic Psupporting
confidence: 59%
“…SB-T-12854 induced cells death in breast cancer cell lines examined (Figure 2). The taxane has also been shown to be effective in cell death induction in other cancer cell lines (7,42). The effect of SB-T-12854 on the growth and survival of breast cancer cells was similar to the effect of previously studied novel non-fluorinated taxane SB-T-1216 (31,32).…”
Section: Figure 4 Effect Of Sb-t-12854 On the Level Of Proteins Of The Bcl-2 Family In Sk-br-3 Mcf-7 And T47d Cells Ie (A) Proapoptotic Psupporting
confidence: 59%
“…paclitaxel and docetaxel, limit the effectiveness of these agents in clinical use. Great efforts have been made to develop novel agents with improved cytotoxicity in resistant tumors but reduced toxicity to healthy cells .…”
Section: Introductionmentioning
confidence: 99%
“…47 It was found that the cell death-inducing effect of these new-generation taxoids is significantly higher than paclitaxel, especially against NCI/ADR cells. Although the effective concentration of new-generation taxoids is much lower than that of paclitaxel, the mechanism leading to apoptosis is essentially the same.…”
Section: Microtubules and Taxoid Anticancer Agentsmentioning
confidence: 99%
“…Caspase-2 may act as the most apical caspase that is responsible for the activation of all other caspases including caspase-9. 47 …”
Section: Microtubules and Taxoid Anticancer Agentsmentioning
confidence: 99%